Analisis Teori Kekuasaan dan Politik Organisasi dalam Pesantren Klasik dan Modern di Indonesia - Dikriyah Dikriyah; Abd. Muid N; Suprihatin Suprihatin (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study analyses the dynamics of power and organisational politics in Islamic educational institutions, particularly classical and modern Islamic boarding schools in Indonesia, using a literature review approach. Islamic boarding schools, which historically centred on the charismatic authority of the kiai, are now transforming in response to the demands of modernisation, which is driving a shift towards more rational and bureaucratic management. A comparative analysis of ten recent scientific articles reveals significant differences in sources of legitimacy, power structures, decision-making mechanisms, external relations, resource management, and conflict resolution between the two models of Islamic boarding schools. Traditional pesantren rely on the personal authority of the kiai and patron-client relationships, while modern pesantren employ legal-rational structures, managerial expertise, and external connections. These findings indicate an urgent need to develop a grand theory of Islamic education management that can accommodate the broad spectrum between community and bureaucratic models, as well as consider socio-cultural and political influences. This study contributes to the theoretical and practical understanding of pesantren governance, highlighting the importance of integrating Islamic values with organisational efficiency